Labour induction and the need for neonatal monitoring following birth in Iceland 2009-2018 - Margrét Þóra Einarsdóttir 1992- (2021)
Background: The labour induction rate has been on the rise during the last decades, especially in industrialised countries. This trend is also occurring in Iceland, and the highest induction rate among the Nordic countries has been measured to be in Iceland. Limited research can be found on the effect of labour induction duration on infants. Elective labour induction is being performed more frequently but studies have found conflicting results on how this affects infants’ risk for needing monitoring after birth. Based on the high labour induction rate, it is important to gain as much information as possible about the effects of labour induction on infants born in Iceland. Objectives: To study the rate of the need for infant monitoring based on labour onset and based on labour induction duration. Indications for labour induction will also be examined with regards to infant monitoring. Methods: Data was obtained from the Icelandic Medical Birth Registry, containing information on all births in Iceland. Included in the analysis were live-born, term singletons born in Iceland 2009-2018. Frequencies and likelihoods were calculated, and chi-square tests used to compare labour onset groups and labour induction duration groups, this was also stratified by parity. Indications for indication were identified using ICD-10 codes, gestational age and maternal age. Results: The study population consisted of 38.443 infants. Among those, 7.593 (19,8%) were born after labour induction. There was a statistically significant difference in monitoring rates by labour onset type. The lowest NICU monitoring rate (4,6%) was amongst infants born after spontaneous labour, but the highest rate was among infants born after labour induction (7,3%). Primipara mothers had a higher labour induction rate (21,5%) than multipara mothers (18,6%). Infants born to primipara mothers did also have a higher NICU monitoring rate than infants born to multipara mothers (9,9% vs. 5,4%). Monitoring rates were also significantly different between groups of ...